Beneficiamento por hidrociclonagem de misturas de argilas bentoníticas pouco nobres de Boa Vista-PB, visando melhoria de suas propriedades reológicas - Marques, Verônica Cavalcanti (2014)
Currently in Brazilian deposits of bentonite clays there are clays with a high percentage of coarse fractions, which have a negative influence on the rheological properties of dispersions prepared with these clays, precluding its use in aqueous drilling fluids of oil wells. The use of a blending with available samples has been industrially used successfully. Therefore, the present study aimed, and using the methodology of modeling blends with simplex centroid network planning with subsequent purification by hydrocycloning and drying in kiln and by spray dryer, optimize the rheological properties of dispersions prepared from mixtures of little noble bentonite clays, from the city of Boa Vista PB, in order to obtain drilling fluids that answer the requirements of the standard EP-1EP-00011-A Petrobras. Through the mixture design was observed that the presence of clay called Verde-Lodo increased values of apparent and plastic viscosities. This fact contributed to this clay was present in all mixtures purified by hydrocycloning. The presence of clay Bofe decreased values of volume of filtrate. Through the intersection of the response surfaces of the mixtures design were obtained eight compositions in which the rheological properties were closer to that specified by the standard and that, therefore, they were more likely to adapt the requirements after the process of purification by hydrocycloning, which showed efficient in promote size separation, with consequent elimination of the coarse fractions of contaminants, especially quartz. Still, it was observed that the purified dried in kiln, which was ground in the mill disks, showed average diameters lower than the purified dried by spray dryer. However, showed a lower rheological behavior to the purified dried by spray dryer, which showed, generally, values of apparent and plastic viscosities above the regulatory requirements. Therefore, it was possible to optimize the rheological properties of a fluid obtained from little noble bentonite clays, enabling the use those low quality clays in drilling fluids for oil wells.